The nitrogen and sulfur status and isotopes of soils within the vicinity of a coal-fired power station in South Africa - Angelova, Mia (My University, 2013)
Amplified loads of sulfate and nitrate have caused increased stress on soil systems in many areas of the world, as both are dominant components of acid rain. This is a critical environmental stress due to the damage caused to soil, water quality and ecosystem functioning. Issues concerning the rising emissions of these elements from local industries have begun to attract increasing attention in South Africa, as the rates of deposition in the Mpumalanga Highveld region alone is comparable to those experienced in First World countries. This study sought to investigate the use of natural stable isotopes of sulfur and nitrogen to identify the process transformations that these species undergo in environmental cycles. Total δ34S, δ15N and δ13C isotope signature of soils in the Mpumalanga region were combined with total elemental concentrations to determine the effect of deposition on the soil system. Soil samples from two soil depths (0 – 10 cm and 20 – 40 cm) were taken along a distance gradient from an identified pollution source, the Majuba power station. Long-term air quality data from the study area were also obtained from Eskom’s air quality monitoring stations, as well as sulfur and nitrogen deposition data from selected literature. Elemental concentrations decreased with soil depth as expected, while sites located approximately 25 km downwind of the power station were seen to contain higher concentrations of both soil sulfur and nitrogen. The mean per site soil sulfur concentration across all depths ranged from 0.009 % to 0.048 %, while the mean per site nitrogen concentration across all depths ranged from 0.056 % to 0.346 %. The mean soil carbon concentration in the top-soils ranged from 0.97 % to 7.93 %, and decreased in the sub-soils to 0.490 % to 3.270 %.The mean δ34S value for the top-soils was found to be 8.28 ‰ and increased to 10.78 ‰ in the sub-soils. Soil δ15N also increased with soil depth from 6.55 ‰ to 8.28 ‰. Soil δ13C values were seen to increase from -12.83 ‰ in the top-soils to -11.90 ‰ in the sub-soils. Lighter δ34S values at the surface may be due to anthropogenic deposition. The positive δ34S shift was attributed to a two-source mixing model (atmospheric deposition and bedrock) and isotopic fractionation processes that occur within the soil profile. The δ15N values of the top-soil were higher than what is expected if all nitrogen was derived from atmospheric nitrogen gas fixation. The increase in δ15N with depth suggested that isotope fractionation occurred during nitrogen export due to the faster reaction rate of 14N compared to 15N. The soil δ13C values indicated a typical C4 grassland system. New carbon at the top-soil depths was enriched in 13C due to the slower decay of 13C-depleted lignin; whereas in the sub-soils microbial recycling of carbon dominates and explained the higher 13C content of the older carbon. The conceptual framework presented for this project involves simultaneous processes of deposition and export in the soil system. This was particularly true for sulfur, where sites with lower isotope values had lower soil sulfur concentrations and vice versa. This indicates that high levels of deposition correspond to high net export. The sulfur and nitrogen isotopic signatures could not be used to as a direct means of source identification; however, the effectiveness of isotopes in elucidating transfer of these nutrients in the soil system was illustrated.
A dissertation submitted to the Faculty of Science, University of Witwatersrand, in fulfilment of the requirements for the degree of Masters of Science Johannesburg, 2012.
Keywords: Stable isotope tracers.; Soil chemistry - South Africa - Mpumalanga.; Nitrogen - Isotopes.; Sulfur - Isotopes.